Investigating the Role of Nursing Technicians in Implementing Electronic Health Record Systems: A Mixed-Methods Approach to Assessing Challenges and Opportunities in Hafr Albatin - Bashair Khamees A Aldhafeeri; Ibtisam Sabar Khalaf Aldhafeeri; Seham Hamed Thani Alshammari; Aishah Matar I Alanazi; Muneefah Braheem T Alshammari; Yousif Saud M Alshammari (International Journal of Medical Toxicology and Legal Medicine, 2024)
Electronic health record (EHR) systems have revolutionized healthcare delivery, but their successful implementation relies on the engagement and proficiency of healthcare professionals, including nursing technicians. This mixed-methods study aimed to investigate the role of nursing technicians in implementing EHR systems and assess the challenges and opportunities they face in Hafr Albatin, Saudi Arabia. A survey was conducted among 150 nursing technicians to evaluate their knowledge, attitudes, and practices regarding EHR systems. Semi-structured interviews were also conducted with 20 nursing technicians to gain deeper insights into their experiences and perspectives. The survey results revealed that nursing technicians had moderate knowledge (mean score: 65.2%, SD: 14.3%) and positive attitudes (mean score: 78.6%, SD: 11.8%) towards EHR systems. However, their practices in using EHR systems were suboptimal (mean score: 58.4%, SD: 16.7%). Thematic analysis of the interviews identified several challenges, including inadequate training, technical issues, and increased workload. Opportunities for improvement included providing comprehensive training programs, enhancing technical support, and fostering a supportive work environment. The findings highlight the need for targeted interventions to empower nursing technicians and optimize their role in EHR implementation. Addressing the identified challenges and leveraging the opportunities can contribute to the successful adoption and utilization of EHR systems in Hafr Albatin and beyond.